DEVELOPMENT OF AN ARGUMENT-DRIVEN INQUIRY (ADI)-BASED SCIENCE E-BOOK ON ECOLOGY MATERIALS - Lestari, Intan; Natadiwijaya, Ismail Fikri (Universitas Pakuan, 2025)
The development of technology in the 21st-century has brought significant changes in the world of education, including the need for more interactive and contextual learning media. One of the challenges in science learning at the junior high school level is the preservation of complex and abstract ecological materials. This research aims to develop an Argument-Driven Inquiry (ADI)-based science e-book on ecological materials as an innovative solution to improve students' understanding of scientific argumentation concepts and skills. The research method used is Research and Development (RD) with a 4D model (define, design, develop, and disseminate) without disseminate stages. The products were validated by material experts and media experts, and tested for practicality by science teachers and junior high school students. The results of the study show that this e-book meets the criteria of